Estudo da degradação de propilparabeno através de fotocatálise utilizando compósito de TiO2/Fe3O4 - Melo, Amanda Lys Matos dos Santos (2022)
With population and industrial expansion, several pollutants are increasing their presence in water bodies. Among these pollutants, the so-called emerging pollutants have low removal efficiency by conventional treatments, presenting a high potential for toxicity. In view of this, technologies are being improved or developed for water treatment, such as advanced oxidative processes (AOPs). As an example of AOP, heterogeneous photocatalysis based on semiconductors is considered a promising alternative to combat emerging pollutants, where a wide variety of compounds can be completely mineralized. In this context, this work carries out a study of the heterogeneous photocatalysis process using TiO2 and the composite TiO2/Fe3O4as catalysts in order to perform the degradation of the pollutant Propylparaben. The use of the TiO2 semiconductor is justified by its high efficiency in photocatalytic processes, while the choice of the TiO2/Fe3O4composite as catalyst is proposed in the work due to the expected influence of the iron magnetic material on the final structure of the composite. The photocatalysts produced were characterized by XRD, SEM and FTIR. The composite obtained showed the predominant crystalline phases anatase and magnetite, as well as photocatalytic activity. The materials efficiency was determined under ultraviolet irradiation through the degradation of propylparaben, in which the highest efficiency was obtained with the composite was 80.83% (20 ppm) and for pure TiO2 it was 94.52% (5 ppm) degradation of propylparaben. The solids present in the solutions treated with the TiO2/Fe3O4 composite were removed by magnetic field induction. These findings corroborate the benefit of using the proposed composite as a valuable alternative to a highly effective photocatalyst for the degradation of emerging pollutants, such as propylparaben.